2009
DOI: 10.1177/0261927x09351681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Regional Accent Variation in Standard Dutch

Abstract: This article investigates native speakers' attitudes toward accent variation in Netherlandic Standard Dutch. Adopting the speaker evaluation paradigm, a demographically controlled sample of listener-judges rated spontaneous speech samples that are representative of four regions in the Netherlands, and from which potentially competing linguistic cues (e.g., pitch and intonation) had not been removed. Speech stimuli were rated on a set of scales integrated from among previous studies conducted in the Low Countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
4
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 17 publications
4
37
4
9
Order By: Relevance
“…It should be noted, first, that the regional identification of the Rand, North, and South accents is less successful in this experiment than in the previous one (Grondelaers et al, 2010), in which the three accents concerned were correctly identified in the range between 75.8% and 90.8%. Especially problematic in the present experiment is the fact that the second North speaker's accent is more frequently identified as a Randstad than as a Northern accent, with evaluations that converge more (in general) with the Randstad speakers' perceptions than with those of the other North speaker.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…It should be noted, first, that the regional identification of the Rand, North, and South accents is less successful in this experiment than in the previous one (Grondelaers et al, 2010), in which the three accents concerned were correctly identified in the range between 75.8% and 90.8%. Especially problematic in the present experiment is the fact that the second North speaker's accent is more frequently identified as a Randstad than as a Northern accent, with evaluations that converge more (in general) with the Randstad speakers' perceptions than with those of the other North speaker.…”
Section: Discussioncontrasting
confidence: 70%
“…This manipulation also enabled us to investigate whether regional accent is still the most potent attitude trigger when competing with explicit social cues. In Grondelaers et al (2010), we found that regional accent is by far the strongest attitude trigger when competing with other low-and high-level linguistic cues. But what happens when a speech sample contains accent triggers as well as social cues?…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations